Kiai’s Leadership Strategies in Strengthening Religious Moderation in Islamic Boarding Schools - Ma`arif, Muhammad Anas; Rokhman, Mauhibur; Fatikh, M. Alfin; Kartiko, Ari; Ahmadi, Ahmadi; Hasan, Moch. Sya’roni (SCAD Independent, 2025)
The spread of radicalism in educational institutions, particularly in Islamic boarding schools, is often attributed to institutional leaders who promote a rigid interpretation of religion. The pivotal role of Kiai (Islamic scholars or leaders) and teachers in these schools is central to developing students’ attitudes toward Rahmatan lil alamin (mercy for all creation) and fostering a moderate perspective. As a role model, Kiai plays a significant role in cultivating a sense of moderation among Santri (students). This article aims to describe and analyze the leadership strategies employed by Kiai in this context. The research adopts a qualitative design with a case study approach and was conducted at the Amanatul Ummah Islamic Boarding School in Pacet, Mojokerto, East Java. The findings highlight several key strategies Kiai Asep Saifuddin Chalim implemented, including strengthening Nahdatul Ulama traditions, implementing a rigorous selection process for teachers and Staff, adhering to fundamental principles of success, and integrating moderate values into the school curriculum. Furthermore, the Kiai’s exemplary leadership supports the development of a wise and balanced attitude among Santri.